Modelling of radio frequency sheath and fast wave coupling on the realistic ion cyclotron resonant antenna surroundings and the outer wall. (11th January 2018) - Lu, L; Colas, L; Jacquot, J; Després, B; Heuraux, S; Faudot, E; Van Eester, D; Crombé, K; Křivská, A; Noterdaeme, J-M; Helou, W; Hillairet, J
Abstract: In order to model the sheath rectification in a realistic geometry over the size of ion cyclotron resonant heating (ICRH) antennas, the self-consistent sheaths and waves for ICH (SSWICH) code couples self-consistently the RF wave propagation and the DC SOL biasing via nonlinear RF and DC sheath boundary conditions applied at plasma/wall interfaces. A first version of SSWICH had 2D (toroidal and radial) geometry, rectangular walls either normal or parallel to the confinement magnetic fieldB 0 and only included the evanescent slow wave (SW) excited parasitically by the ICRH antenna. The main wave for plasma heating, the fast wave (FW) plays no role on the sheath excitation in this version. A new version of the code, 2D SSWICH-full wave, was developed based on the COMSOL software, to accommodate full RF field polarization and shaped walls tilted with respect toB 0 . SSWICH-full wave simulations have shown the mode conversion of FW into SW occurring at the sharp corners where the boundary shape varies rapidly. It has also evidenced 'far-field' sheath oscillations appearing at the shaped walls with a relatively long magnetic connection length to the antenna, that are only accessible to the propagating FW. Joint simulation, conducted by SSWICH-full wave within a multi-2D approach excited using the 3D wave coupling code (RAPLICASOL), has recovered the double-hump poloidal structure measured in the experimental temperature and potential maps when only the SW is modelled. The FW contribution on the potential poloidal structure seems to be affected by the 3D effects, which was ignored in the current stage. Finally, SSWICH-full wave simulation revealed the left–right asymmetry that has been observed extensively in the unbalanced strap feeding experiments, suggesting that the spatial proximity effects in RF sheath excitation, studied for SW only previously, is still important in the vicinity of the wave launcher under full wave polarizations.